Reception analysis of Indonesian audience towards physical and verbal violence on series Squid Game (2021) by Hwang Dong-Hyuk (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2022)
Korean film has been rampantly surging all over the world, particularly in Indonesia. Moreover, Squid Game (2021) by Hwang Dong-Hyuk is popular in the country due to its plot and settings which present the real condition of the gap between upper-class and lower-middle class urban people in South Korea. It becomes intriguing for Indonesian audience because it shows the happening fact not only in South Korea but also similarly in Indonesia. The research was aimed at investigating Indonesian audience’s responses on physical and verbal violence depicted on Squid Game series (2021) by Hwang Dong-Hyuk. The research used the qualitative approach with reception analysis method by Stuart Hall. There are four audiences who become the informants of this research coming from urban workers and Korean film enthusiasts. The data collection technique was done through interviews as well as document analysis. The result showed that the informants’ reception towards the scenes are varying due to the situation and context that set the scenes which present different uses of physical and verbal violence.